2012
DOI: 10.1016/j.neurobiolaging.2011.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy of cerebrovascular amyloidosis in a transgenic mouse model

Abstract: Cerebrovascular amyloidosis is caused by amyloid accumulation in walls of blood vessel walls leading to hemorrhagic stroke and cognitive impairment. Transforming growth factor-β1 (TGF-β1) expression levels correlate with the degree of cerebrovascular amyloid deposition in Alzheimer s disease (AD) and TGF-β1 immunoreactivity in such cases is increased along the cerebral blood vessels. Here we show that a nasally administered proteosome-based adjuvant activates macrophages and decreases vascular amyloid in TGF-β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 52 publications
2
25
0
1
Order By: Relevance
“…The complementary features of TGF mice include thickened vascular walls, impaired dilatory and contractile function, string vessel pathology, 5 chronic cerebral hypoperfusion, 35 neurovascular uncoupling, 36 and cerebral microhemorrhages. 37 Several of these compare very well with what is seen in patients with AD. 38 Both APP (APPSw, Ind, J20 line) 41 and TGF 14 mice display early deficits in dilatory responses to acetylcholine (ACh) and calcitonin gene-related peptide (CGRP), whereas age-related alterations in contractile responses, restricted to endothelin-1 (ET-1) but not affecting those mediated by phenylephrine or serotonin (Fig.…”
Section: Multifaceted Aspects Of Ad Cerebrovascular Pathologysupporting
confidence: 61%
See 1 more Smart Citation
“…The complementary features of TGF mice include thickened vascular walls, impaired dilatory and contractile function, string vessel pathology, 5 chronic cerebral hypoperfusion, 35 neurovascular uncoupling, 36 and cerebral microhemorrhages. 37 Several of these compare very well with what is seen in patients with AD. 38 Both APP (APPSw, Ind, J20 line) 41 and TGF 14 mice display early deficits in dilatory responses to acetylcholine (ACh) and calcitonin gene-related peptide (CGRP), whereas age-related alterations in contractile responses, restricted to endothelin-1 (ET-1) but not affecting those mediated by phenylephrine or serotonin (Fig.…”
Section: Multifaceted Aspects Of Ad Cerebrovascular Pathologysupporting
confidence: 61%
“…82 However, at 16 months of age, TGF mice performed poorly in the novel object recognition test and the Y maze. 37 Together, these studies suggest that the cerebrovascular disease in TGF mice that lack the neurotoxic Ab pathology is insufficient to initiate overt cognitive decline until late in life. Yet, because of their broad cerebrovascular pathology and chronically compromised brain perfusion, TGF mice may display decreased resistance to risk factors commonly associated with cognitive decline, vascular dementia, or AD, such as hypertension, hypercholesterolemia, stroke, and diabetes.…”
Section: Tgf Micementioning
confidence: 97%
“…Recent findings support the importance of endothelial cells and macrophage cross-talk in preventing cerebrovascular amyloid depositions (Lifshitz et al, 2012). This cross-talk may be disrupted following pathologic expression of TGFb1 by astrocytes along the cerebrovascular system (Lifshitz et al, 2012).…”
Section: Role Of Tgf-b1 In Barrier Dysfunction In Alzheimer's Diseasementioning
confidence: 77%
“…Moreover, in mice, transgenic overexpression of TGFβ1 under the control of an astrocyte glial fibrillary acidic protein (GFAP) promoter causes an age‐related deposition of amyloid (starting at 8 months) around cerebral blood vessels and prominent perivascular astrocytosis. Furthermore, these mice have cognitive impairment that may reflect vascular dementia in patients (Lifshitz et al., 2012).…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Few Modified Y-maze studies using AD model mice exist. Age- and genotype-related impairment has been reported at 16 months in TGF-β1 mice, a model for cerebral amyloidosis [54], although no genotype-related impairment has been reported up to 8-12 months in APP/PSEN1 mice [55]. APP/PSEN1 mice show spatial learning deficits in other tasks such as the Morris water maze [21, 37] and it is possible that increasing task difficulty in the present study may have revealed more robust genotype effects [56-58].…”
Section: Discussionmentioning
confidence: 99%